Earthquake multi-classification detection based velocity and displacement data filtering using machine learning algorithms - Murti M.A.; Junior R.; Ahmed A.N.; Elshafie A. (Nature Research, 2023)
acceleration; article; artificial neural network; decision tree; earthquake; filtration; machine learning; random forest; support vector machine; vandalism; vibration; Machine Learning